INTEGRASI NILAI ISLAM DALAM AUDIT: TELAAH LITERATUR TERHADAP ETIKA DAN PENERAPAN MAQASHID SYARIAH - Syndy Safitry; Elyanti Rosmanidar; Alsha Parawansha; Anisa Rahmawati; Novia Sapitri; Arvilla Devina; Karunia Permata Sari (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2025)
Modern audit practices often face ethical challenges such as client pressure, conflicts of interest, and weak auditor integrity, which undermine public trust in audit results. To address these issues, integrating Islamic values into audit practices offers a meaningful alternative by reinforcing moral and spiritual dimensions. This study aims to explore how Islamic ethics and the principles of maqashid sharia can be integrated into auditing practices to develop a more just, accountable, and value-driven audit system. A qualitative approach using library research was applied by reviewing academic sources related to auditing, professional ethics, and maqashid sharia. The findings reveal that Islamic values such as trustworthiness, honesty, and justice form the ethical foundation of the auditing profession. Additionally, maqashid sharia, which includes the protection of religion, life, intellect, lineage, and wealth, serves as a normative framework that expands the audit's objective beyond technical compliance to encompass societal benefit and ethical accountability. The integration of auditing, ethics, and maqashid sharia results in an audit system that is not only legally valid but also spiritually and socially meaningful. In conclusion, sharia-based auditing can serve as a transformative instrument, guiding Islamic financial institutions toward a system that prioritizes morality, transparency, and public benefit.